2021
DOI: 10.3390/su13115819
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Time-Series Investigation of China and U.S. Manufacturing Industries’ Global Supply-Chain-Linked Economic, Mid and End-Point Environmental Impacts

Abstract: Manufacturing activities of China and the U.S. account for a substantial portion of the global manufacturing output and environmental sustainability impacts. The two countries’ economies account for one third of the global economic output. Their supply chains are critically linked with and serve most of the production and service industries across the globe. Recent global trends in manufacturing necessitate a study that comparatively analyzes the two countries’ manufacturing industries from an economic and env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Saber et al [81] conducted a time-series investigation by comparing the global supplychain-linked economic and environmental impacts of manufacturing industries in China and the US. Their study underscores the significance of AI in analyzing the environmental sustainability impacts of these two major economies, which collectively account for a significant portion of global manufacturing output.…”
Section: Ai and DL In Environmental Healthmentioning
confidence: 99%
“…Saber et al [81] conducted a time-series investigation by comparing the global supplychain-linked economic and environmental impacts of manufacturing industries in China and the US. Their study underscores the significance of AI in analyzing the environmental sustainability impacts of these two major economies, which collectively account for a significant portion of global manufacturing output.…”
Section: Ai and DL In Environmental Healthmentioning
confidence: 99%
“…With the development of industrialization, more and more waste and pollutants are being produced, which have exceeded the digestion and absorption capacity of nature. Meanwhile, the consumption of natural resources by industrialization has exceeded its recovery capacity and destroyed the balance of the ecosystem [83]. In order to have a comprehensive understanding of the resource consumption and environmental impact of industrial development, researchers have introduced life cycle assessment as a powerful tool for environmental management to promote sustainable development.…”
Section: Lca and Lccamentioning
confidence: 99%
“…with the assumption of local technology. MRIO methods, conversely, consider international monetary flows more deeply [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, some studies have analyzed the CFP of manufacturing in general, including the freight transport sector. For instance, Saber et al [12] studied the CFP of manufacturing activities in the USA and China. The results showed that China had the largest contributions to the CFP of manufacturing globally, with 91%.…”
Section: Supply Chain Impactsmentioning
confidence: 99%